How Malleable is the Eukaryotic Genome? Extreme Rate of Chromosomal Rearrangement in the Genus Drosophila - Ranz, José Marı́a; Casals, Ferran; Ruiz, Alfredo

(untitled) (Genome Research, 2001)
During the evolution of the genus Drosophila, the molecular organization of the major chromosomal elements has been repeatedly rearranged via the fixation of paracentric inversions. Little detailed information is available, however, on the extent and effect of these changes at the molecular level. In principle, a full description of the rate and pattern of change could reveal the limits, if any, to which the eukaryotic genome can accommodate reorganizations. We have constructed a high-density physical map of the largest chromosomal element in Drosophila repleta (chromosome 2) and compared the order and distances between the markers with those on the homologous chromosomal element (3R) in Drosophila melanogaster. The two species belong to different subgenera (Drosophila andSophophora, respectively), which diverged 40–62 million years (Myr) ago and represent, thus, the farthest lineages within theDrosophila genus. The comparison reveals extensive reshuffling of gene order from centromere to telomere. Using a maximum likelihood method, we estimate that 114 ± 14 paracentric inversions have been fixed in this chromosomal element since the divergence of the two species, that is, 0.9–1.4 inversions fixed per Myr. Comparison with available rates of chromosomal evolution, taking into account genome size, indicates that the Drosophila genome shows the highest rate found so far in any eukaryote. Twenty-one small segments (23–599 kb) comprising at least two independent (nonoverlapping) markers appear to be conserved between D. melanogaster and D. repleta. These results are consistent with the random breakage model and do not provide significant evidence of functional constraint of any kind. They support the notion that the Drosophilagenome is extraordinarily malleable and has a modular organization. The high rate of chromosomal change also suggests a very limited transferability of the positional information from theDrosophila genome to other insects.[The sequence data described in this paper have been submitted to the GenBank data library under accession no, AF319441.]